PENERIMAAN NASABAH NON MUSLIM DI PT BPRS KOTA MOJOKERTO CABANG NGORO JOMBANG DITINJAU DARI UNDANG-UNDANG NOMOR 21 TAHUN 2008 TENTANG PERBANKAN SYARIAH - Zumro'ah, Mentari Binti; Syai'in (Irtifaq, 2022)
Abstract: This paper aims to identify Islamic banking in addressing the acceptance of non-Muslim customers and to find out a review of the Islamic Banking Law Number 21 of 2008 regarding acceptance of non-Muslim customers at PT. BPRS Mojokerto City, Ngoro Jombang branch. The approach method used is in the form of a juridical empirical and phenomenological approach which will be confronted directly with the respondent, namely the business actor in the banking sector. Acceptance of Non-Muslim Customers at PT. BPRS Kota Mojokerto, Branch of Ngoro Jombang in terms of Law Number 21 of 2008 concerning Sharia Banking, namely working with non-Muslims is permissible as long as it does not violate sharia rules and is guided by syariah principles and the principle of prudence, because this is a provision of Islamic banking. Keywords: non-Muslim, Syariah Banking, Islamic Banking Laws.